Large scale-variability in otolith microstructure and microchemistry: The case study of Diplodus sargus sargus (Pisces: Sparidae) in the Mediterranean Sea - Di Franco, Antonio; de Benedetto, G.; de Rinaldis, G.; Raventós, Núria; Sahyoun, R.; Guidetti, P. (Italian Journal of Zoology, 2011)
11 páginas. Pelagic larval duration (PLD) and trace elements in otoliths provide basic information to investigate the dispersal history of marine fishes. Due to the paucity of such information in the Mediterranean region, we assessed PLD, hatching and settlement duration and timing, and otolith microelemental composition of the White Sea bream (Diplodus sargus sargus) from multiple locations (hundreds of kilometers from each other) along the Italian coast (Mediterranean Sea). Otoliths were read to assess PLD and analyzed by a laser ablation inductively coupled plasma mass spectrometer in the core, larval and juvenile regions. PLD ranged from 14 to 17 days and significantly changed among locations, similarly to hatching (temporal windows of 10–24 days) and settlement (8–22 days) duration and timing, and microelemental fingerprints. These results show (1) a non-negligible large-scale variability in juvenile fish traits and otolith chemistry ever tested before for any Mediterranean fish; (2) the usefulness to properly estimate those traits and chemical features that may help shed light on spatial patterns of population connectivity and dispersal of marine fishes. Peer reviewed